2020
DOI: 10.1080/23311908.2020.1716465
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between emotional intelligence and mental health with social anxiety in blind and deaf children

Abstract: The most important human senses are vision and hearing, and learning, educational, communication, and emotional activities are widely associated with these two senses so the purpose of this study was to determine the relationship between emotional intelligence and mental health. The research method was descriptive-correlational and the study population consisted of all students with visual and hearing impairment aged 12 years and above in Kermanshah Exceptional Centers and Public Schools. They were studied (28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
0
7
0
1
Order By: Relevance
“…Moreover, the COVID-19 pandemic has impacted the mental health of families with children with SEND disproportionally. Increases in mental health difficulties could be due to the already higher prevalence of mental health conditions in children with SEND (Simonoff et al, 2008;Neil et al, 2016;Cai et al, 2018;Dehghan et al, 2020;Predescu et al, 2020) and their parents (Asbury et al, 2021). However, another body of growing research suggests that not all families and children with SEND experienced the effects of the pandemic in the same way.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the COVID-19 pandemic has impacted the mental health of families with children with SEND disproportionally. Increases in mental health difficulties could be due to the already higher prevalence of mental health conditions in children with SEND (Simonoff et al, 2008;Neil et al, 2016;Cai et al, 2018;Dehghan et al, 2020;Predescu et al, 2020) and their parents (Asbury et al, 2021). However, another body of growing research suggests that not all families and children with SEND experienced the effects of the pandemic in the same way.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the prevalence of psychiatric conditions in autistic children is high, with one study finding 70% of participants had at least one comorbid condition ( 21 ). Dimensional factors found to impact the mental health of children with SEND include emotion dysregulation ( 22 , 23 ), lower executive functioning ( 24 ), and higher intolerance of uncertainty ( 25 ). Furthermore, there is evidence for a bi-directional relationship between parental and child anxiety ( 26 , 27 ), which may heighten the mental health issues experienced by families with children with SEND.…”
Section: Introductionmentioning
confidence: 99%
“…Azab et al (2015) in a study before the COVID-19 pandemic found that SoAD and GAD subtypes of SCARED in children with mild hearing impairment were significantly lower than moderate and severe hearing impairment [ 35 ]. Dehghan and colleagues also referred to the high SA in deaf adolescent in Kermanshah, western Iran [ 36 ]. A systematic review study also found that deaf and hard of hearing people had higher symptoms of anxiety than hearing people [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…We also found that deaf adolescents had higher mean scores on the school avoidance subtype. Previous studies have shown that students with hearing impairments experience more emotional disorders than other students and have more school phobia [ 36 , 40 ]. This study was conducted at a time when the presence of students in Iranian schools was not banned due to the COVID-19 pandemic, and perhaps one of the reasons for this result is the fear of deaf students attending schools due to the unknown nature of the disease, fear of infection, problems with wearing masks and gloves, lack of training materials related to COVID-19 disease for the deaf.…”
Section: Discussionmentioning
confidence: 99%